2021
DOI: 10.1186/s12889-021-12149-x
|View full text |Cite
|
Sign up to set email alerts
|

Association of multidimensional poverty and tuberculosis in India

Abstract: Background Reduction of multidimensional poverty and tuberculosis are priority development agenda worldwide. The SDGs aims to eradicate poverty in all forms (SDG 1.2) and to end tuberculosis (SDG 3.3.2) by 2030. While poverty is increasingly being measured across multiple domains, reduction of tuberculosis has been an integral part of public health programmes. Though literature suggests a higher prevalence of tuberculosis among the economically poor, no attempt has been made to understand the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 24 publications
0
9
0
1
Order By: Relevance
“…In contrast to diabetes and metabolic syndrome, isolated insulin resistance, under certain conditions, can confer some evolutionary advantage, at the organism level (Soeters and Soeters, 2012 ), and in this case anti-TB immunity. India has long been identified as an endemic zone for tuberculosis (Pathak et al, 2021 ) and is competing with China in becoming the diabetes capital of the world (Joshi and Parikh, 2007 ). The active implementation of the national end TB (NETB) program in India over the past several years might have reduced the LTBI burden (Dolla et al, 2019 ; Bhargava et al, 2021 ), which could have gradually contributed to the increase in diabetes, over the years (“metabolic hygiene hypothesis”) (Aravindhan and Anand, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to diabetes and metabolic syndrome, isolated insulin resistance, under certain conditions, can confer some evolutionary advantage, at the organism level (Soeters and Soeters, 2012 ), and in this case anti-TB immunity. India has long been identified as an endemic zone for tuberculosis (Pathak et al, 2021 ) and is competing with China in becoming the diabetes capital of the world (Joshi and Parikh, 2007 ). The active implementation of the national end TB (NETB) program in India over the past several years might have reduced the LTBI burden (Dolla et al, 2019 ; Bhargava et al, 2021 ), which could have gradually contributed to the increase in diabetes, over the years (“metabolic hygiene hypothesis”) (Aravindhan and Anand, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“… 17 Indian and WHO studies proved that Low body mass index, smoking, alcohol use disorders, indoor air pollution and widespread misuse of anti-tubercular drugs were major risk factors for tuberculosis. 22 , 23 The reduction of tuberculosis prevalence and mortality could be accompanied by growing incomes, improved housing and nutrition situations, and improved health literacy, 24 as proven in Western Europe, North America and some other parts of the world in the 1900s. 2 Moreover, the unfavourable trends in middle-aged (35–55 years) Indian adults indicated that malnutrition, poor hygienic practices and crowded environments resulting from poverty should be addressed as policy priorities.…”
Section: Discussionmentioning
confidence: 99%
“…Desde una perspectiva social, probablemente no exista un mejor marcador del desarrollo humano de una sociedad (Estado-Nación) que su epidemiología de TBC. De esta forma, si se asocian variables como índice de desarrollo humano (IDH) e incidencia de esta enfermedad -inversamente proporcionales-se tiene una idea bastante real del grado de desarrollo de un país [6][7][8] (Figura 1).…”
Section: Punto De Vistaunclassified